The quality control facilities and the upgraded know-how provided by the Project [printed version also available in Arabic] - Bido Z.; Murchid Rachid M.; Jbara G.; Jawhar A.; Soulaiman A.H.; Rayab G.; Lovino R.; Cardone G. (Syrian national strategic plan for olive oil quality : final report, 2007)
The specialists' expert support to the GCSAR lab facilities specialized both in olive oil and table olive analyses is described. Dedicated activities have been carried out in order to upgrade technology, infrastructures, hardware and software with a network connection for data transfer and elaboration. Training activities have been performed all along the project duration (2 and half years) in Italy at Chemiservice, where 4 Engineers of GCSAR have been trained for olive oil analyses during 162 man days and at CRB, where 2 engineers of GCSAR Olive Department (Idleb) learned during 234 man days the main operations concerning the production and quality control of table olives. They have also acquired information about alkaline methods and the natural fermentation for both black and green olives. Two technical laboratories for oil analyses and for following up processing and analyses of table olive (chemical and microbiology analyses) have been established, upgraded and updated at GCSAR Olive Department of Idleb. One panel test room with annexed preparation room (8 seats) for virgin olive oil tasting is now operational in full conformity with EU standards.